2023
DOI: 10.5802/alco.254
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanics of bipartite ribbon graphs: Integrality, Lattices and Kronecker coefficients

Abstract: We define solvable quantum mechanical systems on a Hilbert space spanned by bipartite ribbon graphs with a fixed number of edges. The Hilbert space is also an associative algebra, where the product is derived from permutation group products. The existence and structure of this Hilbert space algebra has a number of consequences. The algebra product, which can be expressed in terms of integer ribbon graph reconnection coefficients, is used to define solvable Hamiltonians with eigenvalues expressed in terms of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…In a series of recent papers, Dr Sanjaye Ramgoolam of Queen Mary University of London and a team of international collaborators started a research programme to take a fresh look at simple mathematical models of string theory and duality [1][2][3][4][5][6] with a view to wider gravity. One study in the early 1990s, for example, identified certain mathematical model universes within string theory which exhibited a striking 'duality' with ordinary quantum theories, with no explicit strings or gravity [10].…”
Section: String Theory As a Tool For Studying The Mathematics Of Algo...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of recent papers, Dr Sanjaye Ramgoolam of Queen Mary University of London and a team of international collaborators started a research programme to take a fresh look at simple mathematical models of string theory and duality [1][2][3][4][5][6] with a view to wider gravity. One study in the early 1990s, for example, identified certain mathematical model universes within string theory which exhibited a striking 'duality' with ordinary quantum theories, with no explicit strings or gravity [10].…”
Section: String Theory As a Tool For Studying The Mathematics Of Algo...mentioning
confidence: 99%
“…It is precisely this kind of large particle limit in quantum field theories that features in the AdS/CFT correspondence. In their papers, Dr Ramgoolam and Dr Ben Geloun developed quantum mechanical models where the quantum states are combinations of ribbon graphs [1,2,6]. In this framework, they found new algorithms for computing group theoretic quantities, called 'Kronecker coefficients', which are of particular interest in complexity theory.…”
Section: Detailsmentioning
confidence: 99%